The Subject, Feminist Theory and Latin American Texts - Sara Castro-Klaren (Studies in 20th & 21st Century Literature, 1996)
From a feminist perspective, this essay reviews and analyzes the interaction between metropolitan feminist theories and their interphase with the academic criticism of texts written by Latin American women. Discussion focuses on the question of the subject, which the author believes to be paramount in feminist theory, in as much as the construction of gender and the historical subordination of women devolve on the play of difference and identity. This paper examines how the problematic assumption by feminist theorists in the North American academy of Freudian and Lacanian theories of the subject pose unresolved problems and unanticipated complications to subsequent deployment of this subject theory as modes of interpretation of texts written by women in Latin America or even to the emancipatory goals on feminists in the academy. This is a case where "traveling theory" must be examined and evaluated very carefully. The second part of the paper concentrates on the feminist challenges that have been already made to both Freudian and Lacanian theories of the feminine. It highlights the work of Jane Flax, Nacy Chodorov, Gayatri Spivak and Judith Butler in suggesting a way out of theories that rely on the primacy of the male subject formation and therefore occlude and preclude the investigation of the modes of women's agency.
Keywords: feminism; feminist theory; latin american feminism; metropolitan feminist theory; academic criticism; gender; gender construction; women; identity; difference; Freudian theory; Lacanian theory; traveling theory; Jane Flaz; Nacy Chodorov; Gayatri Spivak; Judith Butler; male subject; agency